Analisis Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan di Politeknik LP3I Jakarta Kampus Bekasi - Novitri Landong Namora Sihombing (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
The object of the research to be studied has different characteristics compared to other organizations. Thus, it requires qualified employees and lecturers to be able to complete the work appropriately, effectively and efficiently in accordance with the mechanism set by the institution. To obtain this, a good organizational culture is needed that can affect the satisfaction and performance of its employees. Therefore, I want to analyze further about the organizational culture applied by the institution besides to find out the extent to which the conditions of organizational culture and job satisfaction have an influence on employee performance.